2006
DOI: 10.1038/sj.bjc.6603413
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate trends of histological subtypes of nasopharyngeal carcinoma in Hong Kong

Abstract: The overall decline in incidence rate of nasopharyngeal carcinoma in Hong Kong during 1988 -2002 was limited primarily to a decrease in keratinising carcinoma, which could be explained by the decline in cigarette smoking. Genetic and Epstein -Barr virus interactions may explain the relatively stable incidence rate of non-keratinising carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…During the last 10 years, authors from Singapore reported a decrease of NPC incidence especially for UCNT type. This epidemiologic transition could be attributed to a socio-economic level increase as well as diet modification, such as salted fish (rich in nitrosamines) consumption decrease (Tse et al, 2006). The same trend have been observed…”
Section: Transitional Epidemiology Of Npcsupporting
confidence: 67%
See 1 more Smart Citation
“…During the last 10 years, authors from Singapore reported a decrease of NPC incidence especially for UCNT type. This epidemiologic transition could be attributed to a socio-economic level increase as well as diet modification, such as salted fish (rich in nitrosamines) consumption decrease (Tse et al, 2006). The same trend have been observed…”
Section: Transitional Epidemiology Of Npcsupporting
confidence: 67%
“…This high frequency of children and adolescents affected by NPC in Tunisia open the discussion to reach the maximum cure rate with minimal late aftereffects (Boussen et al, 2010). Endemic NPC is highly frequent in south-east Asia with an incidence > 20/100000 compared to NA (Tse et al, 2006). During the last 10 years, authors from Singapore reported a decrease of NPC incidence especially for UCNT type.…”
Section: Transitional Epidemiology Of Npcmentioning
confidence: 99%
“…Among high-to intermediate-risk populations, type III tumors predominate (28,33). The age-incidence curves in this study exhibit a single peak with a decline observed earlier than in the low-incidence populations.…”
Section: Discussionmentioning
confidence: 72%
“…EBV expression in keratinizing squamous cell carcinomas tend to be low and limited to cells with a basaloid appearance with terminally differentiated squamous cells being negative. There has been an overall decline in the incidence of NPC in Hong Kong, but the decline appears to be limited to a decrease in keratinizing squamous cell carcinoma attributable to a decrease in smoking and other environmental factors [23]. …”
Section: Nasopharyngeal Carcinoma Precursor Lesionsmentioning
confidence: 99%